Embedded System and Robotic Education in a Blended Learning Environment Utilizing Remote and Virtual Labs in the Cloud, Accompanied by ’Robotic HomeLab Kit’ - Seiler, Sven; Sell, Raivo; Ptasik, Dennis (International Journal of Emerging Technologies in Learning (iJET), 2012)
It is impossible to imagine everyday life without embedded devices and robotic applications, as they are utilized in almost every nowadays technical product. And there is a frantic need of well-educated developers, designers and programmers to handle and further evolve this existing technology. The domain itself is in a big change because the borders of pure ICT and embedded system are fusing and according to this process new methods for teaching these disciplines are necessary. It is important that ICT education will become more and more to real systems education, instead of just computer software programming, but in most curricula these two domains are still separated. The paper addresses a novel and implemented solution for teaching and learning of Robotics and embedded systems, while setting in remote labs and modern Internet technology into overall learning process. The proposed concept builds the bridge for a simple and logical study process by utilizing ICT for controlling and understanding real word processes and situations. The introduced blended learning concept covers several educational levels, starting from first and second level education up to university education and life-long learning. The solution is covered with hands-on mobile hardware kits, collaborative e-tools and remote labs. The focus in this paper is on the integration of the overall concept and an evaluation of the given courses.